A brief user's guide to single-chain nanoparticles. Issue 2 (31st October 2014) - Lyon, Christopher K.; Prasher, Alka; Hanlon, Ashley M.; Tuten, Bryan T.; Tooley, Christian A.; Frank, Peter G.; Berda, Erik B.
Abstract : In this review we outline the various methods that have been explored to synthesize architecturally defined nanoparticles from discrete polymer chains, summarize the methods of characterization that are required to prove their formation and probe their morphology, and introduce a number of potential applications. Abstract : In this review we outline the various methods that have been explored to synthesize architecturally defined nanoparticles from discrete polymer chains, summarize the methods of characterization that are required to prove their formation and probe their morphology, and introduce a number of potential applications that are being explored currently. Given the small size of the nanostructures produced by these methods and the relative ease with which they can be tailored to specific end use applications it is likely such efforts will intensify in the coming years. So far, simple chemistry has been utilized and high-level characterization and modeling studies have been applied to understand the process by which these particles form and how they behave, both in the bulk and in solution. Although impossible to predict where this work will lead, we hope this "user's guide" will prove useful to the community as research on single-chain nanoparticles continues to evolve.